اتجاهات الطلبة الجامعيين نحو استخدام صحافة الذكاء الاصطناعي دراسة ميدانية على عينة سنة ثانية ماستر سمعي بصري بجامعة الشهيد حمى لخضر – الوادي - طواهري شهلة; سلطاني شمس الأصيل (University Of Eloued جامعة الوادي, 2026)
"تهدف هذه الدراسة إلى استكشاف وفهم اتجاهات الطلبة الجامعيين نحو استخدام صحافة الذكاء الاصطناعي في ظل التحولات التكنولوجية المتسارعة التي تشهدها البيئة الإعلامية. وتنبع أهمية الموضوع من كونه يمس قطاعًا حيويًا يتقاطع فيه الإعلام الرقمي مع الثورة الصناعية الرابعة، حيث تتغير وظائف الصحفيين وأساليب إنتاج الأخبار بشكل جوهري، مما يستدعي فهماً أعمق لكيفية تفاعل الجيل الجامعي، بوصفه فاعلاً مستقبليًا، مع هذه التحولات. اعتمدت الدراسة على المنهج الوصفي التحليلي، وتأسست نظريًا على نموذج القبول التكنولوجي (TAM) ونظرية انتشار المبتكرات (Diffusion of Innovations). وقد وظّفت هاتان النظريتان لتحليل دوافع الاستخدام وسلوكيات التبني التقني لدى الطلبة، من خلال متغيرات مثل المنفعة المدركة، وسهولة الاستخدام، والنية السلوكية، بالإضافة إلى تصنيفات التبني المرحلي للمبتكرات. تم تنفيذ دراسة ميدانية عبر استبيان وُجّه إلى عينة قصدية مكوّنة من طلبة السنة الثانية ماستر في تخصص الإعلام السمعي البصري، باعتبارهم الفئة الأكثر تأهيلاً لفهم الظاهرة قيد الدراسة، نظرًا لتكوينهم الإعلامي المتخصص واحتكاكهم بالتقنيات الحديثة. النتائج الرئيسة للدراسة أظهرت ما يلي: - وجود اتجاهات إيجابية ملحوظة لدى الطلبة نحو تبني صحافة الذكاء الاصطناعي، مع إدراكهم لما توفره من فعالية في جمع البيانات، وسرعة في المعالجة، ودقة في التحرير. - عبّر معظم المبحوثين عن ثقة مشروطة تجاه المحتوى المنتج آليًا، مشيرين إلى ضرورة الحفاظ على البعد الأخلاقي في ممارسة الصحافة الآلية. - تبين أن هناك عوائق بنيوية تؤثر على تبني هذه التقنية، من بينها: ضعف التكوين الجامعي، غياب التأطير البيداغوجي، الحاجز اللغوي، وضعف الثقافة الرقمية المنظمة. - أظهر التحليل توافقاً كبيراً بين نتائج الدراسة والنموذجين النظريين المعتمدين، حيث أثبتت المنفعة المدركة وسهولة الاستخدام تأثيراً مباشراً على النية السلوكية للتبني، كما ساهمت خصائص الابتكار (الميزة النسبية، الانسجام، القابلية للتجربة) في تفسير الفروقات بين المبحوثين. في ضوء النظريات والدراسات السابقة (الدبيسي، 2022 وبريك، 2019)، تبيّن أن التجربة الجزائرية تشترك مع السياقات العربية الأخرى في القلق من الموثوقية ومحدودية التأهيل المهني، لكنها تتميز بوجود استعداد شبابي مرتفع لتبنّي أدوات الذكاء الاصطناعي متى توفرت البيئة الداعمة." "This study aims to explore and understand university students’ attitudes toward the use of artificial intelligence (AI) journalism amid the rapid technological transformations taking place in the media environment. The importance of this topic stems from its relevance to a vital sector where digital media intersects with the Fourth Industrial Revolution, fundamentally altering journalists' roles and news production methods. This necessitates a deeper understanding of how the university generation, as future media actors, interacts with these changes. The study employed a descriptive-analytical approach and was theoretically grounded in the Technology Acceptance Model (TAM) and the Diffusion of Innovations Theory. These two models were used to analyze students’ motivations and behaviors regarding the adoption of AI journalism, focusing on variables such as perceived usefulness, ease of use, behavioral intention, and the innovation adoption stages. A field study was conducted using a questionnaire administered to a purposive sample of second-year Master’s students in audiovisual media, as they are considered the most qualified to grasp the phenomenon under study due to their specialized training and exposure to modern technologies. The main findings of the study revealed the following: - Students expressed notably positive attitudes toward adopting AI journalism, recognizing its effectiveness in data collection, processing speed, and editorial accuracy. - Most respondents showed conditional trust in AI-generated content, stressing the importance of preserving ethical standards in automated journalism. - Structural barriers to adoption were identified, including weak university training, lack of pedagogical guidance, language barriers, and poor digital literacy. - The analysis showed strong alignment between the findings and the theoretical models, as perceived usefulness and ease of use had a direct impact on behavioral intention, while innovation attributes (relative advantage, compatibility, and trialability) helped explain differences among respondents. In light of previous theories and studies (e.g., Dbaissi, 2022; Berrik, 2019), the Algerian experience shares common concerns with other Arab contexts—such as reliability and limited professional training—but stands out with a strong youth readiness to adopt AI tools, provided a supportive environment is in place."
مذكرة ماستر قسم اعلام واتصال تخصص سمعي بصري
Keywords: الاتجاهات; الذكاء الاصطناعي; الصحافة; Journalism; Artificial Intelligence; Trends